Cu(I)‐anchored polyvinyl alcohol coated‐magnetic nanoparticles as heterogeneous nanocatalyst in Ullmann‐type C–N coupling reactions. (10th March 2020) - Hemmati, Saba; Ahany Kamangar, Sheida; Yousefi, Mohammad; Hashemi Salehi, Mirmehdi; Hekmati, Malak
Abstract : In this paper, the preparation of a novel magnetic nanocatalyst (Fe3 O4 @PVA/CuCl) is described, which involves coating of polyvinyl alcohol (PVA) onto the surface of Fe3 O4 nanoparticles and its subsequent coordination with CuCl catalyst. The nanocatalyst was characterized by various analytical methods, including Fourier‐transform infrared, X‐ray diffraction, inductively coupled plasma spectroscopy, field emission scanning electron microscopy, energy‐dispersive X‐ray spectroscopy (EDX), transmission electron microscopy, vibrating‐sample magnetometry, and EDX elemental mapping. Moreover, the nanocatalyst was efficiently used in the N‐arylation of amines via the formation of a carbon–nitrogen bond between the aryl halides and amines by Ullmann‐type coupling reactions. The catalyst was sufficiently stable and can be reused for at least seven times in a model Ullmann reaction without remarkable alteration in its catalytic behavior. Heterogeneity of the catalyst was investigated by a hot filtration test. Abstract : A novel Fe3 O4 @PVA/CuCl magnetic nanocatalyst is described by coating of polyvinylalcohol (PVA) on Fe3 O4 NPs surface and subsequent coordination with CuClcatalyst.